Herbicide resistance in grass weeds: Epigenetic regulation matters too - Sen, Madhab Kumar; Hamouzová, Katerina; Košnarová, Pavlína; Roy, Amit; Soukup, Josef (Frontiers in Plant Science, 2022)
Although herbicides have been successfully used for controlling weeds, the continuous use of them has developed in the evolution of resistance to all major herbicide modes of action worldwide. Reports suggest that the members of Poaceae family are more prone to developing herbicide resistance than other families. In plants, epigenetic mechanisms play critical roles by increasing their stress-adaptive potential in a rapidly changing environment. Epigenetic mechanisms involve alteration of the expression of genetic elements, but without any changes in the DNA sequence. Although the possible roles of epigenetic mechanisms in contributing to survival and fitness under various stresses are well documented in model plants and crops, their contribution to herbicide resistance in weeds is still in its infancy. Several studies with herbicides have shown differential expression of DNA methyltransferases, histone methyltransferases and DNA demethylases in response to the herbicides; however, no further studies were conducted. In the case of herbicide stress, exploring how these epigenetic processes affect the gene expression pattern in individual plants subjected to recurrent selection would be exciting. Hence, our mini-review will focus on the potential contributions of epigenetic mechanisms to the adaptive responses of grass-weedy species to herbicide stress. A better understanding of these epigenetic changes will add novel perceptions to our knowledge of herbicide resistance evolution in weeds enabling the development of herbicides with novel targets.